In-grown structure of NiFe mixed metal oxides and CNT hybrid catalysts for oxygen evolution reaction. Issue 7 (8th December 2015) - Li, Yongmei; He, Haiyong; Fu, Wei; Mu, Chenzhong; Tang, Xiu-Zhi; Liu, Zheng; Chi, Dongzhi; Hu, Xiao
Abstract : The in-grown structure of oxides and CNT hybrids strongly favors the charge transfer at the interface leading to high electrochemical performance. Abstract : This work reports a unique in-grown structure of a NiFe-MMO/CNT hybrid catalyst. This structure creates larger interfacial area and strong interaction between the NiFe-MMO catalyst and the CNT, which could promote charge transfer at the interface, and hence improve conductivity. This leads to outstanding electrochemical performance for oxygen evolution reaction.